Revision of the Agrilus humilis species-group (Coleoptera: Buprestidae: Agrilini) with description of thirteen new species from Southeastern Asia - Jendek, Eduard (Zootaxa, 2017)
The newly defined Agrilus humilis species–group comprising twenty taxa of Indo–Malayan and Australasian region is revised based on the examination of type specimens. The taxonomic concept and distribution of all known species is critically revised for the first time since they were described. The complete commented bibliographic data are given for each name. The key to species is provided and complemented with illustration of habitus and genitalia. Images of all primary types are also included. The following thirteen new species are described: Agrilus aruensis sp. nov.; A. ateles sp. nov.; A. bicoloripennis sp. nov.; A. chloros sp. nov.; A. duffelsorum sp. nov.; A. ecalcaratus sp. nov.; A. incrassatus sp. nov.; A. korbicola sp. nov.; A. oidema sp. nov.; A. sphenopterus sp. nov.; A. suturistriatus sp. nov.; A. thailandicus sp. nov. and A. vogti sp. nov.